YOUTUBE SEBAGAI MEDIA PEMBELAJARAN DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI SISWA- SISWI SD NEGERI 11 TANJUNG BATU KECAMATAN TANJUNG BATU KABUPATEN OGAN ILIR - Cindy Oktarina; Isna Wijayani (Bajang Institute, 2025)
This study aims to discuss YouTube as a learning medium in improving the communication skills of students at SD Negeri 11 Tanjung Batu, Tanjung Batu District, Ogan Ilir Regency. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the use of YouTube can enhance students' communication skills, both verbal and nonverbal, through the presentation of more engaging, interactive, and contemporary content. Supporting factors in the use of YouTube include the availability of technological devices, students' enthusiasm, and teacher support, while limiting factors include internet connectivity issues, lack of content control, and teachers' limited skills in utilizing technology. In conclusion, YouTube is effective as an innovative learning medium in developing elementary school students' communication skills